DEVELOPMENT OF STUDENTS' COMPETENCE IN WORKING WITH INFORMATION IN PHYSICS LESSONS - Muhammadova Dilafruz Akhmatovna (Scholar Express Journal, 2023)
In this article, information is reflected on the issues of developing students' competence in working with information in physics classes, performing laboratory exercises using various software tools, multimedia devices.
Keywords: ability to assess the truth of information; information competence; communicative competence